TAXATION ISSUES IN ROMANIAN PRE-UNIVERSITY EDUCATION PAYROLL COMPARED TO THE EUROPEAN UNION - HADA, Teodor; MĂRGINEAN, Radu; LUKACS, Marina Simona (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The school is one of the bedrocks of the citizens’ development of any country, a reference system for future generations, but the importance given to the educational system varies from country to country, depending on each country’s policy on funding and taxing the education. Our analysis emphasizes theoretically and with practical examples the calculation of payroll in Romanian preuniversity education and the position of our country within the European Union in this field. We have noticed that Romania, in the framework of pre-university education among E.U. countries, is ranked in last place in terms of funding the education system, and in terms of remunerating teachers, having a reduced payroll tax compared to the analysed EU countries, because of the 16% flat tax applied in our country. We believe that an increase in investments in the Romanian pre-university education, by increasing teachers’ wage and ensuring an efficient management of the education system, are factors likely to contribute to the sustainable development of Romanian education in terms of performance and international competitiveness.